Pengaruh Modernisasi Administrasi Perpajakan, Sanksi Perpajakan, Trasparansi dan Kepercayaan Wajib Pajak Terhadap Kepatuhan Wajib Pajak - Abdul Hafizd; Mujiyati Mujiyati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of tax administration modernization, tax sanctions, tax transparency, and taxpayer trust on individual taxpayer compliance registered at the Pratama Tax Office (KPP Pratama) Surakarta. The study employs a quantitative approach. The population consists of 60,573 individual taxpayers registered at KPP Pratama Surakarta. Using the Slovin formula, a sample of 100 individual taxpayers was selected. Data were collected through Google Forms and printed questionnaires and measured using a Likert scale. The research involves several analytical procedures, including descriptive statistical analysis, validity testing, reliability testing, multiple linear regression analysis, normality testing, multicollinearity testing, heteroscedasticity testing, the F-test, the t-test, and the coefficient of determination. All analyses were conducted using SPSS version 25. The findings indicate that tax administration modernization, tax sanctions, tax transparency, and taxpayer trust simultaneously have a significant influence on taxpayer compliance. However, the t-test results show that tax administration modernization and tax sanctions do not have a significant partial effect on taxpayer compliance. In contrast, tax transparency and taxpayer trust are proven to have a significant partial effect on individual taxpayer compliance at KPP Pratama Surakarta